INFLUENCE OF DISCHARGE ON SILICATE WEATHERING DYNAMICS OF THE TIETÊ RIVER BASIN: MAJOR CATIONS AND DISSOLVED SILICA APPROACH - Mortatti, J.; Probst, J. L.; Fernandes, A. M.; Mortatti, B. C.; Oliveira, H. (Geochimica Brasiliensis, 2012)